1976
DOI: 10.3758/bf03335146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interest and relatedness on estimated duration of verbal material

Abstract: Two I-min selections of English prose were recorded, differing on the dimension of interest to the listener. They were re-recorded with the words in random order, so as to differ from the first tapes on the dimension of relatedness. Each tape was heard by 20 volunteer undergraduates who estimated the duration of the selection. Interesting tapes were judged significantly shorter (p < .05) than uninteresting ones, and unrelated tapes were judged slightly (p < .10) shorter than related ones.This contradicts a sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 1 publication
1
11
0
1
Order By: Relevance
“…Listening for a minute to a selection of more or less interesting prose passages has shown that the interesting passages are judged shorter than the others (Hawkins & Tedford 1976). A more original experiment was carried out by Thayer & Schiff (1975), who used a face-to-face eye contact situation between two Ss of the same or opposite sex.…”
Section: Fraissementioning
confidence: 99%
“…Listening for a minute to a selection of more or less interesting prose passages has shown that the interesting passages are judged shorter than the others (Hawkins & Tedford 1976). A more original experiment was carried out by Thayer & Schiff (1975), who used a face-to-face eye contact situation between two Ss of the same or opposite sex.…”
Section: Fraissementioning
confidence: 99%
“…For instance, Hawkins and Tedford (1976) had subjects listen to different prose passages recorded on tape. Subjects judged interesting tapes to be shorter in duration than non interesting ones, in agreement with the predictions of attentional models oftime perception.…”
mentioning
confidence: 99%
“…On dit, par exemple, que le fait d'écouter un récit intéressant donne l'impression que le temps passe plus rapidement (Hawkins et al, 1976).…”
Section: Recherche Fondamentale: éValuation Du Temps Et Des Facteurs unclassified